Origin and Uniqueness of a Polychrome Plaster Sculpture: The Case of a Sacred Heart of Jesus - Ramos, Aline (Revista do Colóquio, 2025)
Plaster is a material used in art production, growing in importance at the end of the 19th century. The ease of reproduction allows for the large-scale production of sacred sculptures and decorative objects, reducing costs and enabling the dissemination of examples. However, sculptures made from this material still present a certain lack of importance for preservation compared to works in wood, a reality that has been gradually changing since the first decade of the 2000s, at which point they have become objects of research. Thus, the restoration of a polychrome plaster sculpture carried out at the Conservation and Restoration Center of the Federal University of Espírito Santo allowed for a series of investigations, both technical and material, as well as into the origin of the image, providing the opportunity to perceive that, although several sculptures are manufactured using the same molds, each piece acquires distinct characteristics according to sociocultural influences.